Comparative Cuticle Development Reveals Taller Sporophytes Are Covered by Thicker Calyptra Cuticles in Mosses - Budke, Jessica M.; Goffinet, Bernard (Frontiers in Plant Science, 2016)
The calyptra is a maternal structure that protects the sporophyte offspring from dehydration, and positively impacts sporophyte survival and fitness in mosses. We explore the relationship between cuticle protection and sporophyte height as a proxy for dehydration stress in Funariaceae species with sporophytes across a range of sizes. Calyptrae and sporophytes from four species were collected from laboratory-grown populations at two developmental stages. Tissues were embedded, sectioned, and examined using transmission electron microscopy. Cuticle thickness was measured from three epidermal cells per organ for each individual and compared statistically. All four species have cuticles consisting of a cuticle proper and a cuticular layer on the calyptra and sporophyte at both developmental stages. Across species, shorter sporophytes are associated with smaller calyptra and thinner calyptra cuticles, whereas taller sporophytes are associated with larger calyptra and thicker calyptra cuticles. Independent of size, young sporophytes have a thin cuticle that thickens later during development, while calyptrae have a mature cuticle produced early during development that persists throughout development. This study adds to our knowledge of maternal effects influencing offspring survival in plants. Released from the pressures to invest in protection for their sporophyte offspring, maternal resources can be allocated to other processes that support sporophyte reproductive success. Using a comparative developmental framework enables us to broaden our understanding of cuticle development across species and provides structural evidence supporting the waterproofing role of the moss calyptra.